HUBUNGAN POLA ASUH OTORITATIF DAN INTENSITAS KOMUNIKASI JARAK JAUH ORANG TUA-ANAK DENGAN KETERBUKAAN DIRI MAHASISWA PERANTAU TERHADAP KELUARGA - Alisha Mumtaz, Farah; Noor Rakhmad, wiwid; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Family ideally provides a sense of security and comfort for individuals, yet not all individuals can freely share personal matters with their families. This study aims to examine the relationship between authoritative parenting styles, long-distance parent-child communication intensity, and the self-disclosure of Out-of-Town students. The theoretical frameworks utilized include John Bowlby's Attachment Theory and Social Exchange Theory. The research involved 60 respondents who are active students at Diponegoro University, originating from outside Semarang and living independently far from their families. Hypothesis testing using Kendall Tau analysis indicated a positive correlation between authoritative parenting styles, long-distance parent-child communication intensity, and Out-of-Town students' openness towards their families. This reveals that the more authoritative the parenting style, the greater the willingness of Out-of-Town students to share personal matters with their families. This aligns with Attachment Theory, which assumes that responsiveness and warmth in parenting tend to foster secure attachment relationships in children, thereby encouraging openness. Additionally, the research findings suggest that higher communication intensity between parents and children during physical separation correlates with greater openness of Out-of-Town students towards their families. This corresponds with Social Exchange Theory, stating that individuals tend to maintain relationships deemed beneficial. The study underscores the importance of consistent and meaningful communication between parents and children in maintaining emotional closeness despite physical distance. It provides insights into how authoritative parenting and high-intensity communication can enhance Out-of-Town students' openness towards their families, thereby aiding in the maintenance of family relationships, especially in long-distance contexts